FAKTOR PENARIK DAN PENDORONG WISATAWAN JEPANG BERKUNJUNG KE BALI - Indah Kusumarini (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
Japanese tourists are one of the most important markets of Balinese tourism, therefore understanding Japanese tourists is very crucial. This research, therefore, aims to identify Japanese tourists' motivations visiting Bali; their needs and wants/ likes of tourist attractions; and the factors which stumble their visit plans to Bali. Theory of motivation ''push and pull/actor